Optimization of Asset Management at the Regional Financial and Asset Management Agency Office of Central Sulawesi Province - Farid Farid; Awaludin Awaludin; Tri Astuti (Universitas Muhammadiyah Palu, 2020)
This research aims to: to know optimal of asset management in Monetary Management Body Office and Asset of Central Sulawesi Province. Optimalisasi did/conducted by Monetary Management Body and Asset of Central Sulawesi Province seen at action process done/completed by that process optimalisasi done/conducted by for example Planning, Research of Goods Requirement ( RKBMD), Compilation RKA, Levying And Record-Keeping ( Asset Stocktaking) as according to Regulation of Ministry of Home Affairs of the Republic Of Indonesia of Number 19 the Year 2016 about Guidance of Goods Management Own the Area. The technique of data collecting used in this research that is an observation technique, interview the documentation. As for method analyze the data in research qualitative done/conducted by if empiric data obtained by that is data qualitative in the form of extant corps of words and non-number network cannot be compiled in category or structure klasifikasi and is ready to use by through/ passing record-keeping, typing, or expert write the. The asset of Ownership Land Monetary Management Body and Asset of Central Sulawesi Province have useful and efesien as according to its role is which do not orient at an advantage as organizer as does SKPD On duty Earnings with the status Borrow To Utilize The. Building Asset Own The Monetary Management Body and Asset of Central Sulawesi Province have according to previous building Levying requirement, have been done/conducted by a goods research to be used. Asset Vehicle Own The Monetary Management Body and Asset of Central Sulawesi Province in the form of a motor vehicle and car just to importance on duty, covering Vehicle individualness, Vehicle on duty operational / Vehicle on duty position/occupation and Vehicle on-duty unique operating / field.